Odin Teatret: Phases of a Theatrical Enclave - Taviani, Ferdinando; Barba, Judy (Peripeti, 2021)
Why a Theatre Laboratory? It includes the programme of a three days’ international symposium from October 4th through 6th 2004. This is the first initiative taken by the Centre for Theatre Laboratory Studies (CTLS), a newly inaugurated centre under Aarhus University in cooperation with Nordisk Teaterlaboratorium. Peripeti include articles on Stanislavski, Meyerhold, Copeau, Decroux, Grotowski, Peter Brook, Théâtre du Soleil, and Odin Teatret and the theatre laboratory praxis of these masters and inventors, including, of course, reflections on their function and effect. In the last article, Eugenio Barba reflects on the creative process of Odin Teatret over the last 40 years. In addition, we also include the curriculum vitae on those participating in the symposium. The occasion of the symposium is to celebrate the 40th anniversary in October 2004 of Nordisk Teaterlaboratorium/Odin Teatret. Congratulations.